Compact Bread Dough Mixer Achieved Three Kilogram Capacity: Mixer Adonan Roti Ringkas dengan Kapasitas Tiga Kilogram - Rachmandani, Arif; Mulyadi (Indonesian Journal of Innovation Studies, 2025)
General Background: Dough mixing is a crucial stage in bread production because it determines mixture uniformity and processing efficiency. Specific Background: Small-scale bakery production requires compact mixing equipment that is affordable, practical, and capable of handling moderate dough loads. Knowledge Gap: Existing studies discuss food-mixing machines, but limited attention has been given to the design of a compact bread dough mixer specifically intended for a 3 kg dough capacity. Aims: This study aims to design a bread dough mixer with a dough capacity of 3 kg by determining the appropriate frame configuration, transmission system, shaft dimensions, and mixing mechanism. Results: The design process produced a functional mixer configuration consisting of a structural frame, drive system, rotating shaft, and mixing blade arrangement sized to support a 3 kg dough load. Component calculations were used to determine the feasibility of the selected dimensions and operating mechanism. Novelty: The study presents an integrated design configuration focused on small-scale bread processing with a specific 3 kg operational target. Implications: The proposed design provides a practical engineering reference for the development of compact dough mixing equipment for household and micro-enterprise bakery applications. Keywords: Bread Dough Mixer, Machine Design, Mixing Capacity, Small-Scale Bakery, Mechanical Design Key Findings Highlights The machine configuration was developed for compact bakery operation. Component calculations supported stable rotational mixing performance. The design accommodated a three-kilogram dough load.